2017
DOI: 10.32771/inajog.v4i4.453
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Cryotherapy in "See and Treat" Program in Jakarta Primary Health Centre

Abstract: Objective: To evaluate the efficacy and safety of cryotherapy in "See and Treat" program in Jakarta Primary Health Care. Method: Using descriptive cross-sectional design, data from medical records were taken with total sampling method. We took the VIA result, cryotherapy procedure, first-marriage age, number of marriage, parity, smoking habit, and the use of contraception. Data were analyzed univariately. Result: Of 86 data, the percentage of cryotherapy to change from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
(20 reference statements)
1
3
0
1
Order By: Relevance
“…This finding was similar to the study done by Campbell et al and Lee et al who reported between 30-39 years (40% and 47%) and Lestari, et al showed 31-40 years (39.9%). [9][10][11] Regarding parity most of the women were parity of two or more (89.1%) in this study which was same as Rijal et al (87.3%). 12 Thapa reported more than 90% in parity two or more whereas Deksisha showed 69.2% of parity more than one.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…This finding was similar to the study done by Campbell et al and Lee et al who reported between 30-39 years (40% and 47%) and Lestari, et al showed 31-40 years (39.9%). [9][10][11] Regarding parity most of the women were parity of two or more (89.1%) in this study which was same as Rijal et al (87.3%). 12 Thapa reported more than 90% in parity two or more whereas Deksisha showed 69.2% of parity more than one.…”
Section: Resultssupporting
confidence: 83%
“…17 Few studies repeated VIA after one year in which 2.1% were VIA positive in Ghana whereas 11% was reported to be VIA positive in study by Phongsavan et al 18,19 The failure of VIA conversion can be caused by several factors such as equipment, healthcare provider, VIA false-positive, referral system factor and presence of other risk factors . 11 Another important finding was that most of the women had done cervical screening for the first time and we can improve on that.…”
Section: Resultsmentioning
confidence: 99%
“…Data dari berbagai penelitian memperlihatkan bahwa upaya untuk meningkatkan luas cakupan skrining dan tindak lanjut krioterapi dalam program see and treat ini masih memberikan hasil yang kurang maksimal. Di negara berkembang, upaya skrining belum tersebar secara merata dan angka cakupannya masih rendah dengan hanya sekitar 5% populasi yang memiliki akses terhadap program skrining 3 .…”
Section: Pendahuluanunclassified
“…7 A study in Jakarta reports that the results of evaluations with VIA six months after cryotherapy show a success rate of 90.7%. 8 Cryotherapy can also inhibit progression of low squamous grade (LSIL) in high grade squamous lesion (HSIL) and in cervical cancer. 9 Other studies have also shown that cryotherapy is effective to prevent cervical intraepithelial neoplasia (CIN) with cure rates of 81.4% for women with CIN 1; 71.4% for CIN 2 and 68.0% for CIN 3.…”
Section: Introductionmentioning
confidence: 99%